2019
DOI: 10.1016/j.humov.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Cancelling discrete and stopping ongoing rhythmic movements: Do they involve the same process of motor inhibition?

Abstract: Motor inhibition is considered to be an important process of executive control and to be implicated in numerous activities in order to cancel prepared actions and, supposedly, to suppress ongoing ones. Usually, it is evaluated using a "stop-signal task" in which participants have to inhibit prepared discrete movements. However, it is unknown whether other movement types involve the same inhibition process. We therefore investigated whether the inhibition process for discrete movements is involved in stopping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 55 publications
5
18
0
Order By: Relevance
“…The behavioral analysis indicated that the SSRTs did not differ between the discrete and rhythmic task and were within the range found in previous studies, including various discrete responses (e.g., Boucher et al, 2007;Kok et al, 2004;Montanari et al, 2017). Critically, the absence of a correlation between the 15 participants' discrete and rhythmic tasks' inhibitory performances, a finding consistent with previous work (Hervault et al, 2019), challenges the notion that the processes inhibiting actions are fundamentally task-independent. This finding is strengthened by the strong positive correlation between blocks of rhythmic tasks, emphasizing that the absence of a correlation between the discrete and rhythmic task does not simply reflect weak performance reproducibility.…”
Section: About Unitary Of Action Inhibitionsupporting
confidence: 81%
See 1 more Smart Citation
“…The behavioral analysis indicated that the SSRTs did not differ between the discrete and rhythmic task and were within the range found in previous studies, including various discrete responses (e.g., Boucher et al, 2007;Kok et al, 2004;Montanari et al, 2017). Critically, the absence of a correlation between the 15 participants' discrete and rhythmic tasks' inhibitory performances, a finding consistent with previous work (Hervault et al, 2019), challenges the notion that the processes inhibiting actions are fundamentally task-independent. This finding is strengthened by the strong positive correlation between blocks of rhythmic tasks, emphasizing that the absence of a correlation between the discrete and rhythmic task does not simply reflect weak performance reproducibility.…”
Section: About Unitary Of Action Inhibitionsupporting
confidence: 81%
“…Therefore, while the perceptual task was clearly continuous, there was hardly any movement to inhibit since there was no displacement or trajectory to speak of. In contrast, a recent investigation showed that the SSRTs associated with cancelling a prepared-discrete key-pressing action (the classic stop-signal task) and stopping an ongoing-rhythmic drawing action were unrelated across participants (Hervault et al, 2019). This finding contradicts the assumption that a single mechanism is involved in inhibiting prepared and ongoing actions.…”
Section: Introductionmentioning
confidence: 83%
“…There are other tasks that address some of the same limitations of the traditional SST that we sought to address here (Alegre et al, 2008;Hervault et al, 2019;Lofredi et al, 2020;Morein-Zamir et al, 2004Morein-Zamir & Meiran, 2003;Slater-Hammel, 1960). Despite the availability of many versions of the stop signal task, the CMST is a valuable addition because it simultaneously allows for direct observation and precise comparison of the timing and mechanisms related termination of continuous movements under both prepared and reactive (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the rhythmic experiment, the movement-related StopTime was calculated as the time elapsed between the STOP signal onset and the end of the movement (i.e., null velocity). Each participant’s RT STOP-R , that is, the time between the STOP signal onset and the onset of movement alteration, was computed by identifying, within the StopTime, the first time point that the movement statistically deviated from the set of uninterrupted movements in the phase space 4 .…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, we know little about cortical sensorimotor engagement related to movement suppression, even though both movement generation and suppression are commonplace in our interaction with the environment 3 . On the other hand, previous investigations of neural activity when suppressing movements have focused exclusively on shortlived discrete movements and have then ignored the case of ongoing-rhythmic movement suppression, which is also crucial in action control [4][5][6][7] . The few studies at hand on sensorimotor activity related to action suppression have dealt with prepared discrete movements [8][9][10][11] , discrete movements sequence 12,13 or isometric force exertion 14,15 .…”
Section: Introductionmentioning
confidence: 99%